Influence of Thymoquinone Exposure on the Micro-Hardness of Dental Enamel: An In Vitro Study - Farooq, Imran; Ali, Saqib; Siddiqui, Intisar Ahmad; Al-Khalifa, Khalifa S.; Al-Hariri, Mohammed (European Journal of Dentistry, 2019)
Objective The aim of this study was to assess changes in micro-hardness level of enamel after it was exposed to thymoquinone (TQ).Materials and Methods Sixteen enamel blocks were prepared and divided into two groups (each group received eight blocks, n = 8); Gp 1 (control): enamel blocks kept in 100 mL artificial saliva (AS) for 24 hours and Gp 2: enamel blocks kept in a mixture of TQ powder (1 g) and AS (100 mL) for 24 hours. Post-immersion they were subjected to simulated brushing with each sample receiving 8,000 linear strokes. For brushing, 3 mL of AS and TQ oil was used for groups 1 and 2, respectively. Enamel surfaces were analyzed for changes in values of surface micro-hardness (pre-immersion, post-immersion, and post-brushing) by obtaining Vickers hardness number (VHN).Results The present study indicated improvement in micro-hardness levels for both groups although experimental group showed more enhancement. The mean baseline VHN for control group was 498.6, 500.4 for post-immersion, and 503.5 for post-brushing. The mean baseline VHN for experimental group was 448.7, 531 for post-immersion, and 610.3 for post-brushing. Statistically significant differences (p < 0.05) were observed when post-brushing VHN values of both groups were compared and also within the experimental group when post-brushing values were compared with baseline values.Statistical Analysis Wilcoxon signed-rank test was applied for the evaluation of pre- and post-exposure hardness values. Level of significance was ≤0.05.Conclusion The exposure of enamel to TQ led to an improvement in its micro-hardness levels. Further studies are required to understand the mechanism of action of TQ on human tissues.
Keywords: enamel; micro-hardness; Nigella sativa; thymoquinone